Best practice in primary care pathology: review 10. Issue 11 (11th May 2007) - Smellie, W S A; Shaw, N; Bowley, R; Stewart, M F; Kelly, A M; Twomey, P J; Chadwick, P R; Houghton, J B; Ng, J P; McCulloch, A J
Abstract : This tenth best practice review examines four series of common primary care questions in laboratory medicine: (i) antenatal testing in pregnant women; (ii) estimated glomerular filtration rate calculation; (iii) safety testing for methotrexate; and (iv) blood glucose measurement in diabetes. The review is presented in question–answer format, referenced for each question series. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most are consensus rather than evidence-based. They will be updated periodically to take account of new information.